Redefining Power: The Role of Women in Governance and Cultural Influence in Ondo, Nigeria – A Comparative Analysis of Traditional and Contemporary Perspectives - OLADAPO, Bisola Henrietta (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This paper explores the cultural construction of power among women in Ondo, a prominent Yoruba kingdom in Southwestern Nigeria, highlighting the dynamics between traditional and modern influences. Despite the pervasive patriarchal structures that often limit women's rights and opportunities, Ondo's cultural heritage reveals an interplay of power where women, particularly through figures like the Lobun and historical rulers such as Oba Pupupu, have played significant roles in governance and community leadership. The study employs a qualitative research design, utilising in-depth interviews and focus group discussions to gather rich, contextual data from women across various age groups and socio-economic backgrounds in Ondo. Participants were selected using purposive sampling to ensure a diverse representation of experiences. Additionally, archival research was conducted to explore historical documents and records that shed light on women's roles in governance throughout Ondo's history. This study critically examines how traditional norms shape women's perceptions and expressions of power, while also addressing the impact of modernity on these constructs. By investigating the strategies women employ to negotiate and assert power within their cultural context, this research aims to deepen the understanding of women's agency and illuminate the intersections between traditional and contemporary dynamics. Ultimately, this work contributes to the broader discourse on women's empowerment, offering insights that can inform policies and interventions aimed at fostering equality and enhancing the status of women in Nigeria and beyond.